Experimentum Cyborg: Investigating the school in a Drama process in Higher Education (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
This article presents an analytical account of an artistic-pedagogical process carried out with a second-semester class from the undergraduate Theater Teaching Degree program at Universidade do Estado de Santa Catarina - UDESC. In this theatrical process, the school was used as a thematic pre-text for scenic investigation through the Drama approach. The structuring and creation process of the drama Experimentum Cyborg, as well as some of the chosen materialities and strategies, were described and analyzed. The text includes a description of the real context of the artistic experimentation and the fictional context developed in the classroom, with an emphasis on the methodology of practice as research.
Keywords: performing arts pedagogy; theater education; drama; school